4 - Everyday Use of Mobile Phones in Niger - Gado Alzouma (Africa Media Review, 2008)
This paper critically examines the effects of mobile phone use on relationships among people in Niger. The study is based on a fieldwork conducted during the summer of 2003 and 2004 among Nigerien urban users of mobile phones in Niamey, the capital city. Semi-structured interviews were used to find out how people ‘experience’ the use of mobile phones in their everyday life. The author argues that the use of mobile phones in Niger is expanding women’s sphere of privacy, challenging the disintegration effects of urban life, reinforcing communal ties, changing social use of time and what Pertierra et al. (2002) call ‘discursive practices.’ The paper concludes by explaining that the popularity of mobile phones in Africa and particularly in Niger lies essentially in the manipulability and low cost of those telecommunications devices, including the fact that mobile phones do not require a certain level of literacy among the users.